New clinical classification of dental arch form using facial axis points derived from three-dimensional models - Bayome Mohamed; Han Seong Ho; Choi Jong-Hyuk; Kim Seong-Hun; Baek Seung-Hak; Kim Dong-Jae; Kook Yoon-Ah (Sciendo, 2011)
Introduction: The purpose of the present study was to use facial axis (FA) points to classify dental arch form generated from an analysis of 3-D virtual models of a sample of normal occlusions. A secondary aim was to introduce a new arch form template based on this classification for clinical application.